A Review on Vulnerability of Climate Change on Livelihood System in Ethiopia - Tilahun, Zewde Alemayehu (International Journal of Scientific Research in Civil Engineering, 2019)
Now a day’s issue of climate change gained a global concern among different development agents and natural resource practitioners. Global climate is varied temporarily and spatially due to different human activities like population growth, over utilizations, degradation of natural resources, urbanizations, technological advancement etc. these activities are leads human life endanger and prone to different social, economical and environmental crises. Therefore the intention of this seminar paper is to review the vulnerability of climate change up on the livelihoods of society in Ethiopia. Developing countries are more susceptible to climate change than developed ones due to their high dependency on agriculture and other natural resource products as well as their low coping and adaptation strategies. This is particular to our country. So, climate variability highly inter linked with livelihoods certain societies and affects the economy poor nations like Ethiopia. Thus, to evaluate climate change impact in the context of multiple stressors that reduce adaptive capacity, many of which are not related to climate or climate change; vulnerability assessment is most helpful. Crop losses may increase if climate change increases climate variability. Major floods which caused loss of life and property occurred in different parts of the country. Understanding how social systems respond to climate change and variability requires knowledge of how they are affected by those conditions today and how they might respond in the future if those conditions change.
Keywords: Agriculture; Coping mechanisms; Drought; Greenhouse; Population